Environmental education use of pesticides: the relations between the agricultural production model, the need for knowledge and the role of schools - Fassis, Fabiana [UNESP]; Carvalho, Luiz Marcelo de [UNESP] (Univ Metodista Piracicaba-unimep, 2015)
From the the first author's master thesis, we try to explore in this article aspects related to construction processes in possible ways on the relation between education and the intensive use of pesticides for agricultural production. The research focused on the relation between Environmental Education and the possibilities for political education and empowerment in contexts where the intensive use of pesticides is a part of the everyday reality of a population. The main research questions are focused on attempts to understand the meanings attributed by educators of a farming community on the issue of using pesticides on crops, and also what justifications and arguments support their statements and their consideration on such practices. The historical-cultural approach guided the production process, organization and analysis of data from interviews with four social agents involved in activities of environmental education in a city in the interior where the main economic activity is related to intensive farming practices. The construction of meaning from the analysis of the interviews allowed us to propose four meaning cores. In this article, we will devote special attention to the core related to the model of agricultural production and the use of pesticides.
Keywords: EDUCATION; ENVIRONMENTAL EDUCATION; EDUCATORS; SCHOOL; PESTICIDES